Contribution of mitochondrial ND1 3394T>C mutation to the phenotypic manifestation of Leber's hereditary optic neuropathy. (31st December 2018) - Ji, Yanchun; Zhang, Juanjuan; Yu, Jialing; Wang, Ying; Lu, Yuanyuan; Liang, Min; Li, Qiang; Jin, Xiaofen; Wei, Yinsheng; Meng, Feilong; Gao, Yinglong; Cang, Xiaohui; et al.
Abstract: Mitochondrial DNA (mtDNA) mutations have been associated with Leber's hereditary optic neuropathy (LHON) and their pathophysiology remains poorly understood. In this study, we investigated the pathophysiology of a LHON susceptibility allele (m.3394T>C, p.30Y>H) in the Mitochondrial (MT)-ND1 gene. The incidence of m.3394T>C mutation was 2.7% in the cohort of 1741 probands with LHON. Extremely low penetrances of LHON were observed in 26 pedigrees carrying only m.3394T>C mutation, while 21 families bearing m.3394T>C, together with m.11778G>A or m.14484T>C mutation, exhibited higher penetrance of LHON than those in families carrying single mtDNA mutation(s). The m.3394T>C mutation disrupted the specific electrostatic interactions between Y30 of p.MT-ND1 with the sidechain of E4 and backbone carbonyl group of M1 of NDUFA1 (NADH dehydrogenase [ubiquinone] 1 alpha subcomplex subunit 1) of complex I, thereby altering the structure and function of complex I. We demonstrated that these cybrids bearing only m.3394T>C mutation caused mild mitochondrial dysfunctions and those harboring both m.3394T>C and m.11778G>A mutations exhibited greater mitochondrial dysfunctions than cybrids carrying only m.11778G>A mutation. In particular, the m.3394T>C mutation altered the stability of p.MT-ND1 and complex I assembly. Furthermore, the m.3394T>C mutation decreased the activities of mitochondrial complexes I, diminished mitochondrial ATP levels and membrane potential and increased the production of reactive oxygen species in the cybrids. These m.3394T>C mutation-induced alterations aggravated mitochondrial dysfunctions associated with the m.11778G>A mutation. These resultant biochemical defects contributed to higher penetrance of LHON in these families carrying both mtDNA mutations. Our findings provide new insights into the pathophysiology of LHON arising from the synergy between mitochondrial ND1 and ND4 mutations.